The role of intrasphincteric botulinum toxin injection in the management of functional biliary pain: a systematic review and meta-analysis. Issue 8 (August 2020) - Menon, Shyam; Kurien, Reuben; Mathew, Ray
Abstract : Background: The management of postcholecystectomy functional biliary pain or Type III sphincter of Oddi dysfunction is challenging. The Evaluating Predictors and Interventions in Sphincter of Oddi Dysfunction study has demonstrated the lack of efficacy of endoscopic sphincterotomy in the management of Type III sphincter of Oddi dysfunction. Objective and methods: Botulinum toxin injection to the sphincter of Oddi has been reported as being effective in uncontrolled studies. We sought to understand its pooled efficacy in controlling pancreaticobiliary pain in a systematic review and meta-analysis. Results: Our literature review yielded 10 studies (416 patients) and on random effects meta-analysis, the pooled efficacy of intrasphincteric botulinum toxin injection in alleviating symptoms of pancreaticobiliary was 49% (complete response) and 64% (partial response). One patient developed mild pancreatitis postprocedure and five patients needed postprocedure hospital admission for pain management. The effect of botulinum toxin injection was transient and in the majority of studies, and a positive response to botulinum toxin injection was followed by an endoscopic sphincterotomy. In one study, relapse of pain was managed by repeat botulinum toxin injections with success. Conclusion: Intermittent botulinum toxin injection could be a potential option in the overall management strategy of patients with Type III sphincter of Oddi dysfunction, in conjunction with medical management with neuromodulatory medication. Abstract : Supplemental Digital Content is available in the text.